47. Quantitative EMG (qEMG). Issue 9 (September 2016) - Gutierrez, Jorge
Abstract : Routine EMG studies are based on subjective, ordinal data representing the motor unit action potential (MUAP) electrical activity expressed in qualitative terms that do not have always physiologic bases and it's very dependent on the examiner experience. Quantitative Electromyography (qEMG) on the other hand evaluates cardinal data and allows to make numerical and statistical comparisons in terms of physical units and it's more objective. qEMG can detect earlier changes in the morphology of the motor units and help better to understand the natures pathologic changes occurring in neuromuscular disorders. Using a trigger and delay line 20 MUAPS can be obtained and analyzed either manually or automatically. The MUAP direct parameters like amplitude, duration, and number of phases are measured in order to distinguish normal from abnormal, and between neuropathic and myopathic disorders. Evaluating the presence of outliers MUAPs improves the sensitivity. Duration is the parameter that better represents the number of fibers and the spatial distribution of the motor units but determination of its onset and termination is difficult. For this reason, some derivate parameters had been developed. qEMG although takes extra time, improves the sensitivity of the EMG evaluation, but special care is required to correct automatic marking errors.